2014
DOI: 10.1186/1471-2458-14-1306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peripheral neuropathy and its associated demographic and health status characteristics, among people on antiretroviral therapy in Rwanda

Abstract: BackgroundThe introduction of antiretroviral therapy (ART) has dramatically reduced the mortality rate of people living with HIV (PLHIV). However, complications of both HIV and ART, such as peripheral neuropathy currently affect PLHIV. The purpose of this study was to establish the prevalence of peripheral neuropathy of the lower extremity and, its association with demographic and health status, characteristics among people on ART in Rwanda.MethodsA cross sectional study was conducted among 507 women and men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 30 publications
(47 reference statements)
3
30
2
Order By: Relevance
“…Unlike studies that found height as an independent risk factor in HIV-PN, several other studies reported no association. For instance, two Rwandese studies found no association between height and PN [ 39 , 40 ]. Studies where gender was not controlled have produced controversial findings too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike studies that found height as an independent risk factor in HIV-PN, several other studies reported no association. For instance, two Rwandese studies found no association between height and PN [ 39 , 40 ]. Studies where gender was not controlled have produced controversial findings too.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not find a similar association. Other studies that reported no association between d4T and PN include studies by Luma et al, [ 31 ] and Tumusiime et al, [ 39 ]. Lack of association was suggested to be due to the limited proportion of d4T users or other risk factors other than d4T [ 35 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences may include variations in comorbidities, age, and ethnicity, which could affect individuals’ responses to self-management strategies to alleviate PN symptoms [ 75 79 ]. For example, HIV patients with neuropathy are more likely to be male and younger than those with diabetic neuropathy or CIPN, as diabetes and cancer incidence increase with age, and PN disproportionately affects women [ 77 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several African studies have investigated the incidence of HIV‐SN and factors associated with its development . However, none of these studies assessed the incidence of SN in a cohort where all individuals were exposed only to TDF‐based cART.…”
Section: Introductionmentioning
confidence: 99%
“…Several African studies have investigated the incidence of HIV-SN and factors associated with its development. [13][14][15][16][17][18][19][20] However, none of these studies assessed the incidence of SN in a cohort where all individuals were exposed only to TDF-based cART. Instead, these studies included individuals who had been exposed to several ART regimens (including stavudine) or who were on cART regimens that did not include TDF (globally, the most common cART initiation regimen).…”
mentioning
confidence: 99%